SURGE OF MALARIA IN MIANWALI DUE TO FLOODS: PERSPECTIVE FROM A SECONDARY CARE HOSPITAL: Surge of Malaria Due to Floods - Ahmad, Saqib Qayyum; Niazi, Ghulam Abbas Khan; Rehman, Aisha (Pakistan Armed Forces Medical Journal, 2015)
Objective: To assess the magnitude of flood related rise in the frequency of malaria, diagnosed at a secondary care hospital, during 2007-2011.Study Design: Cross sectional descriptive study.Place and Duration of Study: Pakistan Air Force hospital Mianwali, from 1st Jan 2007 to 31st Dec 2011.Patients and Methods: Monthly records of hospital laboratory patients with peripheral blood smears, positive for malarial parasites, were counted from 1st Jan 2007 to 31st Dec 2011. Frequencies of vivax and falciparum malarial cases diagnosed each year during 2007-2009 were compared with the corresponding frequencies during the year of floods i.e. 2010, and the following year i.e. 2011.Results: When compared with the mean of the annual frequencies during 2007-2009, there was a rise in the total number of malaria cases by 1.3 times in 2010; while next year, i.e. during 2011, the rise was 3.0 times. During the period 2007-2011, vivax malaria cases always peaked during the months of September each year while falciparum malaria cases had a spike in the months of November.Conclusion: Massive floods resulted in a rise in the frequency of malaria cases during flood season and as an after math during the next malarial season. Planning for prevention and control should be done accordingly. Spread of falciparum malaria following the floods demands more efforts towards halting its possible rise in Mianwali district.